Rancang Bangun Aplikasi Analisis dan Evaluasi Harga Pokok Produksi pada PT AMSI - Baharuddin, Jimmy; Sudarmaningtyas, Pantjawati; Mastan, Ignatius Adrian (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
AMSI is engaged in the field of plastic recycling business located in Surabaya. AMSI serves more than one hundred shoppers scattered inside and outside the country. Still don't have AMSI mechanism in the process of evaluation, which is the production cost analysis calculations. Model of analysis appropriate for current analysis of three difference raw material cost, the analysis of difference for direct labor costs and analysis of four factory overhead costs for the difference. AMSI applications require can help conduct analysis and evaluation to control production costs. Application analysis and evaluation of the cost of production of the goods that can help make a difference in the cost analysis and providing reports to evaluate the production cost at AMSI.